Penerapan Metode Psikologi Bermain sebagai Upaya untuk Mengurangi Kejenuhan Belajar Siswa SD Pertiwi Makassar - Jafar, Eka Sufartianinsih; Safitri, Annisa; Mutmainnah, Mutmainnah; Susanti, Susanti (IPTEK: Jurnal Hasil Pengabdian kepada Masyarakat, 2023)
Abstrak. The learning process is an important factor that will affect student learning outcomes. One of the problems that can occur in the learning process is learning plateau. Learning plateau can be overcome by implementation the psychological method of play. The psychological method of play  is the giving of games that can be given at the beginning, on the sidelines, or at the end of the learning process. The games given in this activity are jenga, estafet bola, tebak hewan and tepuk pagi siang malam. The aims of this activity is to determine the effect of games in reducing student learning plateau in grades 1, 2, and 3 at SD Pertiwi Makassar. Data collection was carried out by observing and interviewing before and after the games was given. The result of the study represent that games in the learning process can reduce student learning plateau.Kata Kunci: Metode Bermain, Psikologi, Kejenuhan Belajar